Load Dependence Behavior of The Thermoelectric Module Energy Harvesting System by Inverse Dynamic Analysis–Maximum Power Point Tracking - Mohamed, R.; M. Yusop, A.; Mohamed, A.; A. Sulaiman, N. (International Journal of Engineering and Technology, 2019)
This paper presents the characterization behavior of a thermoelectric module (TEM) analysis by the implementation of a new inverse dynamic analysis–maximum power point tracking (IDA-MPPT), with different load resistance values to the common maximum power point circuit (MPPC) controller. In this study, a conventional TEM test unit measurement is performed consists of a hotplate and a TEM module. The two MPPC boards are fed with the harvested voltage from the TEM module and a supercapacitor is linked with it. The load resistor is then fed with the boosted voltage of the second board.  The three phases experimental analysis is introduced in a closed loop manner.  There are, TEM system analysis without the IDA-MPPT implementation, TEM system analysis with IDA-MPPT implementation, and a newly developed IDA-MPPT unit experimental analysis. Results have shown that the TEM system with IDA-MPPT implementation with 1kΩ resistor is capable of achieving 5V output stable line voltages with 83.33% efficiency.  In conclusion, with the input stable voltage of the MPPC board from the new input –shaping process, a satisfactory load behavior is achievable by its voltage readings.